A database for multi-dimensional effects of tropical forage technologies in Sub-Saharan Africa - Paul, Birthe K.; Koge, Jessica; Nderi, Alex N.; Maass, Brigitte L.; Notenbaert, An Maria Omer; Groot, Jeroen C.J. (2021)
Small-scale livestock productivity in Sub-Saharan Africa (SSA) has been limited mainly by the lack of adequate quality feeds. This database contains data on effects of tropical forage technologies from 72 pre-selected experimental studies from across SSA. The experimental studies were selected and compiled following a well-defined systematic literature search of peer-reviewed articles in Scopus conducted in June 2016. The systematic search of studies was complemented with references cited in the primary literature including unpublished studies from the authors’ personal networks. The database contains data from four technology clusters (improved feed regime, improved germplasm, improvement management, improved cropping system integration), and includes effects on quality and quantity of forage, livestock productivity, soil quality, economic performance, and food crop productivity.